Studi Batuan Asal (Provenance) Batupasir Formasi Simpangaur Daerah Way Krui, Lampung - Alviyanda Alviyanda; Candra Sadaperarih Sipayung (Journal of Science and Applicative Technology, 2023)
Bengkulu basin is the one of fore arc basin which formed in Sumatra island. The basin formation is inseparable from tectonic activity of the Sumatra Island from the Pre-Tertiary era to present day. The relationship between tectonic activities and the basin filling can be identified by conducting a provenance study on the sedimentary rocks. The Simpangaur Formation is a Tertiary sedimentary rock that has filled the Bengkulu Basin in the southern Sumatra. The aim of this research is determining the provenance of Simpangaur Formation existed in Way Krui area, Lampung, and its tectonic environment. The observations of thin section were carried out on eleven sedimentary rock samples obtained from field. The provenance of these rocks is analyzed by quantifying the mineral composition microscopically. The result analysis show that the grains originated from a magmatic arc environment, specifically the transitional arc and undissected arc. Based on the presence of polycrystalline quartz in eleven rock samples, it is interpreted as originating from the Orogen Arc. In addition, it is also interpreted that the provenance for sandstone samples of the Simpangaur Formation are plutonic and metamorphic rocks in a semi-arid climate, based on ancient climate.